Relationship of Vitamin D-Deficient Diet and Irisin, and Their Impact on Energy Homeostasis in Rats - Abulmeaty, Mahmoud Mustafa Ali; Almajwal, Ali M.; Alam, Iftikhar; Razak, Suhail; ElSadek, Mohamed F.; Aljuraiban, Ghadeer S.; Hussein, Khulood S.; Malash, Asmaa M. (Frontiers in Physiology, 2020)
Background and Objective Previous studies have identified the role of irisin and vitamin D in energy homeostasis. However, the effect of irisin and vitamin D on energy regulation has not been thoroughly investigated. Therefore, in this study, the effects of a vitamin D-deficient diet and irisin on total energy expenditure (TEE), food intake, and blood metabolites were investigated in rats. Methods Sixteen healthy weaned male albino rats were randomly divided into two groups: a group fed a normal balanced growth diet (group A: n = 8) and a group fed a normocalcemic diet that is vitamin D deficient with limited ultraviolet (UV) light exposure (group B, n = 8). After 6 weeks, the volumes of respiratory gases were measured by open-circuit indirect calorimetry. Serum irisin, 25-OHVD3, calcium, insulin, and glucose levels were measured using ELISA. The respiratory quotient (RQ), energy expenditure, and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) were calculated. Results Rats with hypovitaminosis D were hypoirisinemic. Food intake, RQ (to the range of using endogenous fat), and glucose levels reduced significantly, while insulin levels increased. Body weight and TEE were non-significant changed. Additionally, irisin was strongly and positively correlated with body weight under normal conditions (r = 0.905, p < 0.01), and a moderate negative correlation in group B (r = −0.429, p < 0.05). TEE and irisin showed no significant correlation. Conclusion This study demonstrated that the early changes in energy homeostasis and irisin levels during states of hypovitaminosis D are affected by long-term consumption of a vitamin D-deficient diet with limited UV exposure.